Pollen Dimorphism of Several Members of Nymphaeaceae and Nelumbonaceae: An Index of Geographical and Ecological Variation - Somnath BHOWMIK; Badal Kumar DATTA (Notulae Scientia Biologicae, 2012)
Pollen morphology of five Nymphaea (Nymphaeaceae) species, growing in Tripura, India were analysed using Scanning Electron Microscopy. Pollen grains of Nymphaea are dimorphic (ellipsoidal and spheroidal). The exine pattern also varies among the species. The variation as reported in the present study in terms of exine pattern of the studied species suggests the feasibility of applying the data in the identification of the genus of Nymphaea. The difference in exine patterns with the earlier reports may be interpreted as reflections of genetic variations possibly due to mutational changes effected by ecological conditions. The present pollen dimorphism may be attributed by introgression of populations. The variability in pollen morphology, including size variation and morphological differences, is often associated with hybrids among angiosperm groups. The examinations of percentages of aborted grains, generally considered a good indicator of hybridity. The occurrence of monosulcate pollens in Nelumbo nucifera along with dominant tricolpate pollens may be considered as aberrant pollens because of very low percentage of occurrence of monosulcate pollens. The ecological and geographical variations in pollen morphology could be an index of the genetic impact of the environment on the plant. Thus the present difference in terms of exine pattern could be useful to separate them at varietal level.